Post-conflict reconstruction in the Middle East and North Africa region: A bidirectional parametric urban design approach. (September 2020) - Steinø, Nicolai; Dabaieh, Marwa; Ben Bih, Karima
Post-conflict reconstruction is a major topic in war-torn cities in the Middle East and North Africa region. Rather than being limited to re-establishing pre-conflict conditions, new formats of urban settings may be adopted, both for the design and quality of urban space, as well as for the design and building process. This article proposes a combined top-down and bottom-up design approach, supported by parametric urban design modelling. As sustainable (re-)development of the urban-scape requires coordination across different scales, a top-down approach is partly needed for reasons of coordination. As participatory design processes involving local stakeholders work from the partial to the whole, a bottom-up approach is partly needed for reasons of inclusion. By means of a parametric urban model combining both overview and detail, the two approaches can be combined. This article shows the theoretical framework and, by way of example, applies the model to Fallujah in Iraq as a case study.